Biomanufacturing (Spinger, 2004)
Advances in bioproducts manufacturing such as the production of the anticancer drug paclitaxel by large-scale plant cell culture, submerged cultivation of medicinal mushrooms, and monoclonal antibody production are reflected. Interactions among molecular, cellular and process engineering aspects in industrial fermentations are discussed, and application of fuzzy control and fuzzy neural networks to practical production and the biomedical area are shown. For sustainable development and green processing, production of lactic acid from paper sludge, production of a generic fermentation feedstock from wheat, and fabrication and application of whole-cell based biosensors in the environment are also demonstrated.